Research on Comprehensive Control Strategy of Loop Closing Currentin 10 kV Distribution Network - LIU Song; HUANG Chun (Kongzhi Yu Xinxi Jishu)
The loop closing operation may lead to excessive current which could lead to an impact on the safe and operation stability of the distribution network, although it can improve the power reliability. To solve the problem of loop closing current adjustment in 10 kV distribution network, a comprehensive control strategy based on improved multi-objective harmony optimization algorithm was proposed in this paper. A comprehensive control model of loop closing current, which considers the safety and economy of loop closing operation, is established to realize the objective of minimal loop closing current and minimal power loss by adjusting transformer taps and switching capacitor banks. An improved harmony algorithm based on dynamic parameters and Pareto optimal is used to solve the model, then a recursive algorithm is used to solve the action sequence of control elements considering process security. Finally, simulation based on Matlab/Simulink platform was performed for a practical case of loop closing operation, and results show that the proposed algorithm has better ability to achieve global optimal solution compared with the traditional harmony search algorithm.